Pink tax: Challenges faced by Indonesian women as consumers of personal care products - Utami, Arvhi Mega; Prastiwi, Juwita Hayyuning (UIN Ar-Raniry Banda Aceh, 2024)
The phenomenon of pink tax is a gender inequality issue that discriminates women in the purchase of goods or services by producers. The objective of this research is to identify the pink tax phenomenon in Indonesia, encompassing its existence, influencing factors, and the urgency of the related issue. Additionally, this study aims to analyse the role of the government through policies regarding the emergence of the pink tax phenomenon. Policies closely associated with the pink tax include Law Number 8 of 1999 on Consumer Protection, Law Number 5 of 1999 on the Prohibition of Monopoly Practices and Unfair Business Competition, and Law Number 7 of 2014 on Trade. The research methodology employed in this study is qualitative, involving literature review, documentary analysis, and interviews. The findings of this research indicate that the pink tax exists in Indonesia, yet awareness of this issue is not evenly distributed across all layers of society. While some institutions have acknowledged the existence of this problem, there have been no concrete steps taken to reduce or address this gender-based price discrimination. Furthermore, current policies are deemed inadequate in addressing gender-based price discrimination practices and protect women’s consumer. This is attributed to the fact that gender equality elements are not fully encompassed in the existing policies.